2001
DOI: 10.1038/sj.onc.1204893
|View full text |Cite
|
Sign up to set email alerts
|

β2-microglobulin induces apoptosis in HL-60 human leukemia cell line and its multidrug resistant variants overexpressing MRP1 but lacking Bax or overexpressing P-glycoprotein

Abstract: In this study, we examined whether exogenous b 2 -microglobulin (b 2 m) can induce apoptosis in the drug sensitive HL-60 leukemia cell line and its drug resistant variants and investigated the molecular mechanism of b 2 m-induced apoptosis. Our data revealed that b 2 m is very signi®cantly down-regulated in two multidrug resistant variants of the HL-60 cells: (a) the MRP1-bearing, Bax-de®cient HL-60/ADR cell line, and (b) the P-glycoprotein (P-gp) overexpressing HL-60/VCR cell line. However, exogenous b 2 m in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 83 publications
3
23
0
Order By: Relevance
“…Our results show that the HL-60/ADR cells are about 122.5-14-and 8.5-fold more resistant to DOX, VCR and VBL, respectively, compared to their parental HL-60 cells (Table 1). Consistent with these data, we have previously reported that HL-60/ADR cells overexpress MRP1, but not P-gp (Wu et al, 2001).…”
Section: Drug Resistance Characteristics and Analysis Of Pr3 And Mrp1supporting
confidence: 90%
“…Our results show that the HL-60/ADR cells are about 122.5-14-and 8.5-fold more resistant to DOX, VCR and VBL, respectively, compared to their parental HL-60 cells (Table 1). Consistent with these data, we have previously reported that HL-60/ADR cells overexpress MRP1, but not P-gp (Wu et al, 2001).…”
Section: Drug Resistance Characteristics and Analysis Of Pr3 And Mrp1supporting
confidence: 90%
“…HL-60/VCR cells in contrast were established as vincristineresistant cells and overexpress P-glycoprotein. Both multidrug resistant cell lines show enhanced efflux rates of various agents and hence display resistance to multiple anticancer drugs [46]. Both multidrug-resistant cell lines showed 35% apoptosis after 15 hrs in the presence of 50 µM PSI whereas HL-60 cells revealed an increase to 83% (Fig.…”
Section: Analysis Of Selected Proteins In Multidrug-resistant Hl-60 Cmentioning
confidence: 96%
“…All antibodies used were previously assessed by immunohistochemistry [for Dr4 and Dr5 (18); for cleaved caspase-3 (19)] or by Western blot analysis [for AIF (20); for cleaved caspase-3 (21)]. the antibodies p53 and Ki-67 are routinely used by the pathology Department.…”
Section: Patientmentioning
confidence: 99%